The effect of physical exercise during competitions and in simulated conditions on hormonal-neurophysiological relationships in kickboxers - Rydzik, Łukasz; Obmiński, Zbigniew; Wąsacz, Wojciech; Kopańska, Marta; Kubacki, Rafał; Bagińska, Małgorzata; Tota, Łukasz; Ambroży, Tadeusz; Witkowski, Kazimierz; Pałka, Tomasz (Biology of Sport, 2024)
K1-format kickboxing is a widely followed combat sport that requires intense physical exercise. However, research into the body’s response to this type of combat is sparse. This study aims to assess the alterations in hormone levels and brain activity in elite kickboxers following an actual K1 bout and compare these changes with those observed in a control group engaged in a simulated fight exercise with a punchbag. The study included 100 male professional kickboxers, randomly divided into two groups: an experimental group (K1 fight) and a control group (simulated fight with a punchbag). Blood samples were obtained before and after exercise to evaluate testosterone (T) and cortisol concentrations (C). Concurrently, brain activity was recorded using quantitative electroencephalography (QEEG). After the activity in the experimental group mean testosterone level slightly, non‑significantly decreased from 13.7 nmol/l to 12.4 nmol/l, while mean cortisol significantly (p < 0.001) increased from 313 to 570 nmol/l. In the control group after the exertion against a punchbag mean cortisol significantly (p < 0.001) increased from 334 to 452 nmol/l and testosterone increased non‑significantly, from 15.1 to 16.3 nmol/l. In both groups, the testosterone/cortisol ratio (T/C ratio) showed significantly lower levels after the intervention (p < 0.001 and p < 0.032) in the experimental and control group respectively. The comparison of groups after exercise revealed significantly higher cortisol levels (experimental group x = 570 nmol/l; control group x = 452 nmol/l) and a significantly lower T/C ratio (experimental group x = 2.7; control group x = 3.9), (p = 0.001) in the experimental group. Significantly higher brain activity was found in selected leads after a bout (experimental group). Furthermore, in the experimental group, significant associations of weak to moderate strength were found between hormone fluctuations and selected areas of brain activity (p < 0.05). K1-format kickboxing induces a stress response, evident in the sharp changes in cortisol and testosterone levels. A notable observation was the inverse direction of changes in both hormones. Brain activity analysis indicated the potential influence of raised cortisol concentrations on specific brain areas. This study augments our understanding of the physiological responses during K1 kickboxing bouts and may inform the future evolution of this sport.